Ratanakiri Economic Development Based on the Rectangular Strategy - Tep, Veasna; Son, Oudom; Ros, Ravuth (Journal of Applied Research and Innovation (JARI), 2026)
This study examined the economic development of Ratanakiri , Cambodia, within the framework of rectangular strategy (2018–2023), emphasizing infrastructure, human resource development, agriculture, and private sector promotion. By employing a mixed-methods design, data were collected from 154 samples of 250 stakeholders, including provincial officials, households, and small- and medium-sized enterprises (SMEs). Quantitative analysis was conducted to assess provincial outcomes in relation to national development objectives. Qualitative analysis was employed to determine the perceptions of economic development. Results revealed notable improvements in road accessibility, electricity coverage, internet penetration, literacy rates, health service provision, and SME employment. Despite these gains, the province continued to face significant challenges, including geographical isolation, socio-ethnic disparities, and limited institutional capacity, which constrained full realization of development goals. By using Amartya Sen’s Development Theory as the analytical lens (Sen, 1999), this study interpreted development not solely as the economic growth but as the expansion of human capabilities and freedoms, highlighting the importance of enabling people to lead lives they value. Based on these findings, the study recommends strategic investments in infrastructure, enhanced education and vocational training programs, support for inclusive private sector growth, and strengthened governance and institutional capacity to maximize the effectiveness of the Rectangular Strategy. This study contributed to promote equitable, sustainable, and human-centered development in Ratanakiri, offering insights for policymakers and development practitioners in similar remote provinces.